Ruminations on the NSF Broader Impacts Criterion: A Dialogue with Academic Researchers and Broader Impacts Professionals - Yunus Doğan Telliel; Katherine C. Chen (The University of Alabama, 2024)
The National Science Foundation, a United States federal agency supporting STEM research, puts special emphasis on research impacts in society, and requires each funded research project to have "broader impacts" outside of conventional academic scholarship. As "broader impacts" have become an important part of the STEM research landscape in the U.S., most academic researchers need guidance and support in their broader impact plans. Focusing on a mid-size STEM-focused university, our research identified three major areas that matter to academic researchers: (1) autonomy of the researcher and non-prescriptive nature of broader impacts, (2) impact identity and personal connection to broader impacts, and (3) a critical engagement with diversity and inclusion in research and education. Combining these findings with a broader impacts professional's reflections, we examine the ways in which broader impacts resources such as the ARIS Toolkit can assist academic researchers. We argue that by constructing dialogues between faculty researchers and broader impacts professionals, the research culture in the U.S. can turn into an ecosystem that supports meaningful, inclusive, and transformative STEM practices.